2022
DOI: 10.1136/bmjopen-2021-058708
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions for dry eye: a protocol for an overview of systematic reviews

Abstract: IntroductionDry eye is a leading cause of ocular morbidity and economic and societal burden for patients and healthcare systems. There are several treatment options available for dry eye and high-quality systematic reviews synthesise the evidence for their effectiveness and potential harms.Methods and analysisWe will search the Cochrane Eyes and Vision US satellite (CEV@US) database of eyes and vision systematic reviews for systematic reviews on interventions for dry eye. CEV@US conducted an initial search of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In this issue of JAMA Ophthalmology, McCann et al 1 are to be commended for undertaking a critical review of the literature on the efficacy and adverse effects of various dry eye therapies. Overall, 71 systematic reviews evaluating interventions for dry eye were included, and of the 26 systemic reviews deemed reliable, no conclusive evidence was identified for the effectiveness of any dry eye intervention.…”
Section: Invited Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of JAMA Ophthalmology, McCann et al 1 are to be commended for undertaking a critical review of the literature on the efficacy and adverse effects of various dry eye therapies. Overall, 71 systematic reviews evaluating interventions for dry eye were included, and of the 26 systemic reviews deemed reliable, no conclusive evidence was identified for the effectiveness of any dry eye intervention.…”
Section: Invited Commentarymentioning
confidence: 99%
“…Beyond issues with the trials themselves, it is important to also consider the limitations of systematic review designs and meta-analysis strategies. Only 37% of the systematic reviews included in the study by McCann et al 1 were deemed reliable, with incomprehensive literature search and inappropriate meta-analysis being the key methodologic limitations. The spectrum of quality among systematic reviews on ocular surface disease corroborate with findings from the recent Tear Film and Ocular Surface Society Evidence Quality Report 8 and emphasizes the importance of considering potential bias in the evidence synthesis process and whether or not the methods are appropriate for evaluating the research question.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the money spent on managing dry eye disease, there is a well-documented disconnect between the ocular surface signs of dry eye disease and patient-reported symptoms 8–10 . Although treatments may yield improvements in signs, patients may not experience improvement in symptoms or vice versa 8–10 .…”
mentioning
confidence: 99%
“…Despite the money spent on managing dry eye disease, there is a well-documented disconnect between the ocular surface signs of dry eye disease and patient-reported symptoms 8–10 . Although treatments may yield improvements in signs, patients may not experience improvement in symptoms or vice versa 8–10 . Inadequate symptom relief may explain why patients often need additional interventions, such as over-the-counter artificial tears that are intended to directly lubricate the ocular surface and may be effective in alleviating symptoms of dry eye disease for short periods 11,12 .…”
mentioning
confidence: 99%